2018
DOI: 10.1063/1.5026770
|View full text |Cite
|
Sign up to set email alerts
|

Optical signatures of deep level defects in Ga2O3

Abstract: We used depth-resolved cathodoluminescence spectroscopy and surface photovoltage spectroscopy to measure the effects of near-surface plasma processing and neutron irradiation on native point defects in β-Ga2O3. The near-surface sensitivity and depth resolution of these optical techniques enabled us to identify spectral changes associated with removing or creating these defects, leading to identification of one oxygen vacancy-related and two gallium vacancy-related energy levels in the β-Ga2O3 bandgap. The comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 50 publications
7
86
0
Order By: Relevance
“…25,26 The most likely candidates seem to be deep acceptors with the optical ionization threshold near 2.3 eV and 3.4 eV. 25,26,29 Their presence in very high concentration is not confirmed in our high temperature/low frequency C-V measurements with illumination. The proposed hydrogen passivation of donors would be in contrast to theoretical predictions and to some experimental results obtained for H introduction at high temperatures during growth.…”
mentioning
confidence: 64%
“…25,26 The most likely candidates seem to be deep acceptors with the optical ionization threshold near 2.3 eV and 3.4 eV. 25,26,29 Their presence in very high concentration is not confirmed in our high temperature/low frequency C-V measurements with illumination. The proposed hydrogen passivation of donors would be in contrast to theoretical predictions and to some experimental results obtained for H introduction at high temperatures during growth.…”
mentioning
confidence: 64%
“…12 There has been a recent report on neutron irradiation effects using depth-resolved cathodoluminescence and surface photovoltage spectroscopy to explore optical defect transitions >1.1 eV within the β-Ga 2 O 3 bandgap. 19 Here, we use a combination of DLTS and deep level optical spectroscopy (DLOS) to quantify the energy levels and concentration distributions of defect states throughout the ∼4.8 eV bandgap of unintentionally doped (UID) β-Ga 2 O 3 substrates grown by the EFG method, before and after neutron irradiation at several doses. The specific neutron irradiation-induced defect states causing carrier removal via a compensation mechanism are identified, and the evolution of the deep level defect distribution for two displacement damage doses of neutron radiation is compared and quantified using DLTS and DLOS.…”
Section: Articlementioning
confidence: 99%
“…An alternative explanation for the n-type conductivity is from the inadvertent incorporation of impurities, especially Sn or H, that act as shallow donors [5]. Additionally, theoretical and experimental studies have suggested that gallium vacancies (V Ga ) are native acceptors and are responsible for the compensation of n-type conductivity [7][8][9]. Recently, substitutional Fe at Ga sites (Fe Ga ) has been found to be an energetically favorable acceptor defect in edge-defined film-fed grown (EFG) β-Ga 2 O 3 crystals, which dominates deep-level defect traps [10].…”
Section: Introductionmentioning
confidence: 99%
“…Computational and electron paramagnetic resonance (EPR) studies clearly demonstrated that self-trapped holes are thermally stable in β-Ga 2 O 3 [16,17], which serve as a precursor for the formation of self-trapped excitons (STEs) that are responsible for the dominant UV emission in β-Ga 2 O 3 single crystals [3,15]. The BL emission has been found to be strong in conducting Ga 2 O 3 samples and as a result has been assigned to the recombination of an electron bound to a V O defect [3,9,14], Several Ga 2 O 3 -based devices have been reported with an optical response in the UV range that exhibit a dramatic change in the electronic transport with increasing operation temperature [2,18], indicating the importance of controlling and understanding temperaturedependent carrier recombination kinetics in Ga 2 O 3 . In this paper we investigate characteristics of luminescence bands in Ga 2 O 3 and provide evidence of the involvement of carrier trapping in an electron injection-induced optical emission.…”
Section: Introductionmentioning
confidence: 99%